Influencia de los Módulos de aprendizaje basados en Imágenes, en la mejora de la Producción de Textos Narrativos en los estudiantes del 3° grado de Educación Primaria de la Institución Educativa “Rafael Narváez Cadenillas” - Trujillo, 2015 - Bacilio Benites, Emelyn Lucia (2017)
The present work of investigation has for purpose demonstrate that the application of Modules of Learning performs great importance to improve significantly the level of production of narrative texts of the students, and to achieve that they approach the reading of agreeable and voluntary form, allowing so they produce and believe narrative texts orientated to improving his learning._x000D_ This investigation I take as an axis of study the problems of production of texts that there present the students of three degree of primary education of the I.E "Rafael Narvaez Cadenillas", of the province of Trujillo._x000D_ The study conformed with a population shaped by 39 students; 20 of the section "A" and 19 of the section "B"; the investigation is applied by design cuasi experimentally with pre and posttest; being the experimental group the section "A" and the group control the section "B"._x000D_ After the application of the Modules of Learning to the experimental group, the obtained results us demonstrate that the students of the above mentioned group, have managed to improve significantly the levels of Production of Narrative Texts.